2005
DOI: 10.1117/1.1852554
|View full text |Cite
|
Sign up to set email alerts
|

Near-infrared frequency-domain optical spectroscopy and magnetic resonance imaging: a combined approach to studying cerebral maturation in neonatal rabbits

Abstract: The neonatal rabbit brain shows prolonged postnatal development both structurally and physiologically. We use noninvasive near-IR frequency-domain optical spectroscopy (NIRS) and magnetic resonance imaging (MRI) to follow early developmental changes in cerebral oxygenation and anatomy, respectively. Four groups of animals are measured: NIRS in normals, MRI in normals, and both NIRS and MRI with hypoxia-ischemia (HI) (diffusion MRI staging). NIRS and/or MRI are performed from P3 (postnatal day=P) up to P76. NIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…3), similar to changes reported for neonatal rabbits (D'Arceuil et al, 2005; D'Arceuil et al, 2008; Drobyshevsky et al, 2005), rodents (Calabrese and Johnson, 2013), kittens (Baratti et al, 1999) and humans (Mukherjee et al, 2001). It has long been established that myelination is not a prerequisite to the origin of diffusion anisotropy in WM (Beaulieu, 2002), and WM tracts are substantially anisotropic on diffusion weighted images even in fetuses and neonates much before the onset of myelination (Drobyshevsky et al, 2005; Wimberger et al, 1995).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…3), similar to changes reported for neonatal rabbits (D'Arceuil et al, 2005; D'Arceuil et al, 2008; Drobyshevsky et al, 2005), rodents (Calabrese and Johnson, 2013), kittens (Baratti et al, 1999) and humans (Mukherjee et al, 2001). It has long been established that myelination is not a prerequisite to the origin of diffusion anisotropy in WM (Beaulieu, 2002), and WM tracts are substantially anisotropic on diffusion weighted images even in fetuses and neonates much before the onset of myelination (Drobyshevsky et al, 2005; Wimberger et al, 1995).…”
Section: Discussionsupporting
confidence: 81%
“…This period of development in rabbits is characterized by reaching important behavioral milestones: eye opening, increase of locomotive abilities, hopping and first exploratory behavior. Maturation of DTI indices continues is rabbits during at least four postnatal weeks (D'Arceuil et al, 2005). Similar, rapid phase of FA change between P12 and P24 coincides with the onset of active myelination in rats (Calabrese and Johnson, 2013; Jito et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that all white matter structures show increasing FA with age and this has been published for in vivo rabbit brain [D'Arceuil et al, 2005], for human brain [Neil et al, 1998Prayer et al, 2001;Wolf et al, 2001;Forbes et al, 2002;Mukherjee et al, 2002;Schmithorst et al, 2002;Schneider et al, 2004;Ben Bashat et al, 2005;Gupta et al, 2005;Snook et al, 2005;Dubois et al, 2006] and for other animal brains [Mori et al, 2001;Kroenke et al, 2005;Zhang et al, 2005]. The structural coherence of the cerebral white matter (in perfusionfixed tissue) is known to be preserved postmortem [Sun et al, 2003[Sun et al, , 2005 and we have shown increased FA in all major white matter structures with increasing postnatal age in our postmortem, perfusion-fixed brains.…”
Section: Discussionmentioning
confidence: 99%
“…The rabbits' brains are lissencephalic, i.e., there is no cortical folding, and the average cortical thickness, measured on in vivo T 2 -weighted magnetic resonance images, increases at least up to the 6th postnatal week. In addition, myelination continues in the corpus callosum, internal capsule and the centrum semiovale up to at least the 4th week postpartum [D'Arceuil et al, 2005]. In comparison, the brains of human neonates continue to myelinate postnatally, in particular the corticospinal (CST) and corticobulbar (CBT) tracts continue to myelinate until 2 years of age [Sarnat, 1989].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation